2018
DOI: 10.1186/s41936-018-0066-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of soil physico-chemical properties on distribution of earthworm populations across different land use patterns in southern India

Abstract: Background: The distribution of earthworms is usually diverse and their population fluctuates in relation to the different physico-chemical properties and land use patterns of the soil of southern parts of India. This particular study examined distribution and relative abundance of earthworms under different land use patterns and their influence on the physico-chemical properties of the soil. We measured the species composition of earthworm communities across the three different land use ecosystems and effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Total nitrogen and organic matter under refuse disposal soils were two to three fold higher than that in agricultural and savannah soils (Table 1). Evidence of earthworm population influencing soil physical and chemical properties has been shown, particularly regarding such parameters as soil structure, water holding capacity, organic carbon, total nitrogen and phosphorus (Sankar & Paitnak 2018). The magnitude of earthworm influence, nevertheless, varies between species and/or ecophysiological groups.…”
Section: Resultsmentioning
confidence: 99%
“…Total nitrogen and organic matter under refuse disposal soils were two to three fold higher than that in agricultural and savannah soils (Table 1). Evidence of earthworm population influencing soil physical and chemical properties has been shown, particularly regarding such parameters as soil structure, water holding capacity, organic carbon, total nitrogen and phosphorus (Sankar & Paitnak 2018). The magnitude of earthworm influence, nevertheless, varies between species and/or ecophysiological groups.…”
Section: Resultsmentioning
confidence: 99%
“…The modification of these structures through channels is formed by the movement of earthworms accompanied by the formation of various classes of aggregates that are unstable (Barré et al, 2009;Zhu et al, 2020). The physico-chemical changes associated with the formation of these new structures could include soil pH, C, N, P, C/N, K, and CEC, and these depend on species, soil type, and land use (Sankar and Patnaik, 2018;Bottinelli et al, 2020;Tamartash and Ehsani, 2021). Nadalia and Pulunggona (2020) reported that the soil pH without topsoil at a depth of 0-20 cm is in the range of 5.61 -6.69 in the mining area of Soroako, South Sulawesi.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the AMF spore density increased with increasing earthworm-ant ratio, confirming the presence of ants plays an important role in improving the soil pH, organic-C, N, and P contents (Almeida et al, 2019;Boots et al, 2012). Therefore, improved pH, organic-C, N, and P through bioturbation by ants,createsmore suitable conditions for earthworm activity to form new biostructures (Sankar & Patnaik, 2018;Taylor et al, 2019). In addition, the biostructures' environmental condition derived from the treatments modulates the growth of AMF spore populations (de Menezes et al, 2018;Lucas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%